2021
DOI: 10.3389/fpsyg.2021.646074
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Views on Play and the Goal of Early Childhood Education in Relation to Children's Home Activity and Executive Functions: A Cross-Cultural Investigation

Abstract: The present study investigated the cross-cultural variations in parents' views on the role of play in child development and the primary purpose of preschool education from Ethiopia and Hungary. It also examined the cross-cultural variations in preschoolers' executive functions (EF), the frequency of their engagement in home activities, and the role of these activities in the development of EF skills. Participants included 266 preschoolers (Ethiopia: 139 of which 44.6% boys; Mage = 63.83 months; SD = 7.68 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…These rapid changes that occur in EF during the preschool years make it difficult to determine the structure and organization of EF at this stage of life ( Scionti et al, 2020 ), which justifies the existence of different models in the literature about the processes that make up children’s EF ( Stalnacke et al, 2019 ). While there is consensus about the multidomain structure of EF in adulthood, the structure of EF in childhood is still an open question ( Metaferia et al, 2021 ). Different studies have found empirical evidence both in favor of a one-dimensional model and of multidimensional models formed by two factors/functions or even three, which nature varies according to studies ( Miyake and Friedman, 2012 ; Diamond, 2013 ; Stalnacke et al, 2019 ; Hartung et al, 2020 ; Scionti et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These rapid changes that occur in EF during the preschool years make it difficult to determine the structure and organization of EF at this stage of life ( Scionti et al, 2020 ), which justifies the existence of different models in the literature about the processes that make up children’s EF ( Stalnacke et al, 2019 ). While there is consensus about the multidomain structure of EF in adulthood, the structure of EF in childhood is still an open question ( Metaferia et al, 2021 ). Different studies have found empirical evidence both in favor of a one-dimensional model and of multidimensional models formed by two factors/functions or even three, which nature varies according to studies ( Miyake and Friedman, 2012 ; Diamond, 2013 ; Stalnacke et al, 2019 ; Hartung et al, 2020 ; Scionti et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because of regional and national differences, ideological and political education vary greatly from one region or country to the next [ 21 ]. When it comes to education in the United States, students are encouraged to cultivate their own ideals and virtues while also obtaining a well-rounded education that includes civics, life skills, and the study of religion [ 22 ]. It is important for schools in the United States to emphasise the importance of ideological and political education.…”
Section: Introductionmentioning
confidence: 99%
“…A more fundamental challenge was the culturally alien concept of a caregiver playing with the child. In Ethiopia, play between parent and child is uncommon and not typically thought of as an opportunity for parent–child interaction or learning ( Metaferia et al, 2021 ). However, parents spend time with their children in household activities such as feeding and bathing, and these activities (also included in the CST) come more naturally to Ethiopian parents than the play activities.…”
Section: Discussionmentioning
confidence: 99%